Generalities about Design and Operation of Microgrids (2015)
The need of new generation systems have motivated the development of microgrids. This new concept may bring significant benefits to the transmission and distribution networks as losses reduction, high degree of efficiency and reliability. This paper presents generalities about microgrids, including general structure and different topologies; also it is proposed an original methodology for facilitating its design and evaluation. Finally, it's analyzed the microgrid located at the Parque Tecnológíco de Guatiguará at the Universidad Industrial de Santander, included an operation analysis for different operations stages of loads and generation,  the performance of operation of storage systems, the interaction with the grid and an energy balance for all the system.